Overcoming barriers to low carbon agriculture and forest restoration in Brazil: The Rural Sustentável project. (December 2016) - Newton, Peter; Gomez, Angelo Eduardo Angel; Jung, Suhyun; Kelly, Timothy; Mendes, Thiago de Araújo; Rasmussen, Laura Vang; Reis, Júlio César dos; Rodrigues, Renato de Aragão Ribeiro; Tipper, Richard; van der Horst, Dan; Watkins, Cristy
Highlights: Multiple barriers have prevented wider uptake of Brazil's ABC Program credit loans. The Rural Sustentável (RS) project tackles these barriers via multiple mechanisms. RS provides farmers with access to information, training, credit, and incentives. Low carbon agricultural practices include forest restoration and integrated systems. Forest restoration may generate environmental and livelihood benefits. Abstract: The Rural Sustentável project aims to decrease greenhouse gas emissions, reduce poverty, and promote sustainable rural development in the Brazilian Amazon and Atlantic Forest biomes: by restoring deforested and degraded land, and by facilitating and promoting the uptake of low carbon agricultural technologies. The project offers farmers a) access to information, through demonstration units and field days; b) access to technical assistance, through in-person and online training and capacity-building; c) access to rural credit, through collaborative farmer-technician partnerships, and d) financial incentives, in the form of results based financing to successful farmer-technician teams. The project is still in its implementation stage, but the innovative design and theory of change of this project offer insights into possible mechanisms for promoting forest restoration on private lands in the tropics.